A profile of the personhood and career of Janine M. Bernard: virtues of a supervision leader. Issue 1 (2nd January 2020) - Luke, Melissa; Goodrich, Kristopher M.
ABSTRACT: Dr. Janine M. Bernard is a notable Counselor Educator, whose career has spanned more than four decades. Through her Discrimination Model and subsequent scholarship in supervision, Bernard has profoundly influenced the interdisciplinary training, practice, and ongoing professional development of supervisors across counseling and its sister mental health fields. In this profile, the authors illuminate the multidimensional themes exemplifying Dr. Bernard's personhood and career. Specifically, we highlight the virtues of candor, benevolence, pragmatism, industriousness, humor, and generativity that have influenced her life and career, describing how she embodies and enacts each.